Static characteristics and engineering applications of micro negative Poisson’s ratio bolt - TAO Zhi-gang; GUO Ai-peng; HE Man-chao; ZHANG Jin; XIA Min; WANG Ding; LI Meng-nan; ZHU Zhen (Rock and Soil Mechanics, 2022)
Compared with traditional small deformation bolt materials, the negative Poisson’s ratio (NPR) bolt/cable material has excellent mechanical properties such as large elongation, high strength, high toughness, high constant resistance, and energy absorption. Based on the research and application of macro-NPR bolts/cables, He Manchao developed a new type of micro-NPR steel material and a new type of micro-NPR bolt. At present, there are few studies on the static characteristics of the micro-NPR steel, and the applicability of the micro-NPR anchor in urban underground tunnel engineering needs to be verified by field tests. The mechanical properties of the micro-NPR steel were studied by the static tensile test in laboratory. The results show that the average elongation ratio of this batch of micro-NPR steel is 34.68%, and the constant resistance range is 203.9-240.7 kN. The tensile deformation is uniform in the whole process, and there is no yielding platform and no obvious necking when breaking. Through theoretical derivation, the elastoplastic incremental constitutive model of the micro-NPR bolt under micro-static tensile condition was established. Taking the air duct section of a subway station as the engineering background, this paper introduced the construction technology of the micro-NPR bolt, and tested the ultimate pull-out force, elongation ratio, and axial force on site. The results show that the micro-NPR bolt has the advantages of high constant resistance and large elongation. The application test of the bolt supporting was carried out in the tunnel with the large-deformation surrounding rock, and the large deformation control effects of the surrounding rock were verified.